2005
DOI: 10.1159/000086962
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Clomiphene Citrate on Ovarian, Endometrial, and Cervical Histologies in a Rat Model

Abstract: Objective: To examine the effect of clomiphene citrate (CC) on the ovarian, endometrial, and cervical histologies in a rat model. Methods: The rats (n = 40) were randomly assigned to 4 treatment groups: CC 50 (repetitive doses of 0.2 mg CC); CC 100 (repetitive doses of 0.4 mg CC); CC 200 (repetitive doses of 0.8 mg CC), and control (repetitive doses of normal saline). Each study group received its CC dose intraperitoneally in 2 ml saline for 5 days and the controls received 2 ml saline only. Each treatment cyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Gonadotropins have been shown to induce granulosa cell tumors in rodents 67 and stimulate cells in human in vitro models, 68 and clomiphene has been shown to increase granulosa, theca, and luteal cells in a rat model. 69 Epidemiological studies of these rare tumor types are not available, but several descriptive analyses in Finland 70,71 fail to provide support for an effect of fertility drug use on granulosa cell tumors.…”
Section: Disease Heterogeneitymentioning
confidence: 99%
“…Gonadotropins have been shown to induce granulosa cell tumors in rodents 67 and stimulate cells in human in vitro models, 68 and clomiphene has been shown to increase granulosa, theca, and luteal cells in a rat model. 69 Epidemiological studies of these rare tumor types are not available, but several descriptive analyses in Finland 70,71 fail to provide support for an effect of fertility drug use on granulosa cell tumors.…”
Section: Disease Heterogeneitymentioning
confidence: 99%
“…This assumption could be supported by some reporters, who studied the effect of clomiphen on rat ovarian histology. They found that clomiphen could increase the number of granulosa cells and they raised the possibility that clomiphen may increase the risk of granulosa cell tumours especially if used in high doses [26] . In another study done, the ability of the human embryonic stem cells to differentiate into functioning granulosa cells was tested.…”
Section: Discussionmentioning
confidence: 99%
“…They also concluded that CC could be a risk factor for granulosa, theca and luteal cell tumors. 17 In the last decades many investigators focused on the relationship between infertility treatment and cancer. The most commonly used ovulation inducing medications, CC and gonadotropins, were implicated in the etiology of ovarian cancer.…”
mentioning
confidence: 99%